HUBUNGAN KUALITAS TIDUR DENGAN NYERI KEPALA PRIMER PADA MAHASISWA PREKLINIK FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN 2020 - Zain Maliki (2021)
Sleep disorder and primary headache are common diseases among teenagers and both relate reciprocally. This research was aimed to determine the relation between sleep quality and primary headache among preclinic medical students in UPN Veteran Jakarta, 2020. The sample of this research were 90 of students aged 17-23 years old. This research was an analytic observational research using cross sectional design. This research used purposive sampling method to determine the number of sample inquiried. Pittsburgh Sleep Quality Index (PSQI) was used to analyse the sleep quality and HO K-H dan Ong BK-C questionnaire was used to analyse the primary headache. Bivariate analysis using cross-sectional was conducted in this research. The significance value of this research is 0,370 (p>0,05). It was concluded that there was no relation between sleep quality and primary headache among preclinic medical students UPN Veteran Jakarta, 2020.